Фундаментальні та прикладні засади інтродукції та збереження фітогенетичного різноманіття нових культур в Україні - Rakhmetov, Dzhamal (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2026)
The Department of Cultural Flora, as a leading scientific center, has achieved significant results in studying the phytodiversity. The research focuses on improving the processes of plant acclimatization and adaptation, creating original phytogenetic resources, and on the conservation, enrichment, and rational use of new, non-traditional, underutilized, introduced, and autochthonous useful plants. From its establishment to the present, the department has passed through three historical periods of development: the first (1945–1968) is associated with Academician Mykola Gryshko and Professor Danylo Lykhvar; the second (1969–2001) with Professor Yuriy Uteush; and the third (2002–present) is defined by the development of modern research directions. During the latest period, 17 major scientific projects were implemented to develop mechanisms for regulating growth, metabolic, and production processes in plants. These studies have unlocked the potential of new crops in Ukraine by leveraging original genetic resources and technological protocols to address critical issues in green energy, food security, organic production, and phytoremediation. Scientific and methodological foundations for the mobilization of new plant resources have been developed, resulting in the creation of gene pool collections of living plants (3,000 accessions) and a seed bank (approx. 10,000 accessions). The Collection Fund of Energy and Aromatic Plants (over 1,800 taxa) is officially recognized as a National Heritage of Ukraine. On this basis, unique genotypes (about 40 new crops) and highly adaptive plant cultivars with specified production parameters (150 original cultivars, nearly 100 of which were developed in the modern period) have been created. Mechanisms have been studied and modern methods developed to increase the resistance of newly introduced regional plant species to abiotic and biotic stressors. A new genotypic base of plants with C4-type photosynthesis has been established, characterized by significantly higher potential for resilience and accumulation of valuable metabolites. The scientific and practical foundations for the introduction and utilization of new phytogenetic resources as highly efficient sources of protein, lipids, sugars, vitamins, biofuels, food products, feed, and green fertilizers, as well as for the restoration of marginal, eroded, and contaminated lands, have been theoretically substantiated and practically implemented.